2019
DOI: 10.1002/pon.5293
|View full text |Cite
|
Sign up to set email alerts
|

Psychobehavioral risk factors for financial hardship and poor functional outcomes in survivors of multiple primary cancers

Abstract: Objective Survivors of multiple primary cancers (MPC) are at increased risk for poor health outcomes compared with survivors of single cancers. Using an adapted psychobehavioral stress‐response model, the study purpose was to identify pathways and individual risk factors associated with poor health outcomes in adults with MPC. Methods Adult MPC survivors (N = 211) with first cancers (stages I‐III) diagnosed within 1 to 10 years were recruited via tumor registry. Employing a cross‐sectional design, established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The dimensions that were found to be significantly associated with FH are also consistent with prior literature QOL constructs such as role changes, pain, and emotional/ psychological well-being. 12,44,45 New literature 40 suggests that a COST cutoff score of 17.5, which is similar to our median sample score of 16.8, may provide acceptable sensitivity and specificity to predict QOL as measured by the Functional Assessment of Cancer Therapy-General. While self-reported race was a variable included in model testing (that did not produce significant associations in multivariate testing), we recognize that race is a social construct, not a biological variable, and suggest that future studies continue to explicitly measure and examine root causes underpinning health and well-being, such as systemic racism.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The dimensions that were found to be significantly associated with FH are also consistent with prior literature QOL constructs such as role changes, pain, and emotional/ psychological well-being. 12,44,45 New literature 40 suggests that a COST cutoff score of 17.5, which is similar to our median sample score of 16.8, may provide acceptable sensitivity and specificity to predict QOL as measured by the Functional Assessment of Cancer Therapy-General. While self-reported race was a variable included in model testing (that did not produce significant associations in multivariate testing), we recognize that race is a social construct, not a biological variable, and suggest that future studies continue to explicitly measure and examine root causes underpinning health and well-being, such as systemic racism.…”
Section: Resultssupporting
confidence: 65%
“…8 Financial hardship has been associated with marked negative outcomes, including increased symptom burden, decreased quality of life (QOL), bankruptcy, and increased mortality. [9][10][11][12][13] Despite the known negative influence of FH on health and QOL, studies have demonstrated that adequate patient-provider communication about FH does not consistently occur in the clinical setting, 14,15 which may contribute to increased symptom burden and suffering.…”
mentioning
confidence: 99%
“…Several modifiable factors, including provider-patient discussions about costs, social support, and perceived stress, may affect FT in cancer patients. 18,75,76 Well-designed studies are warranted to examine the association between these factors and FT in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been linked to a proinflammatory state that causes nociceptive hypersensitivity with a heightened perception of pain [19,20] and psychological distress [21,22]. Betcher et al have correlated a higher BMI, lower level of education, greater neuroticism, and less social support with self-controlled behavior and greater anguish [22]. Obesity has been associated with increased depression that fosters weight gain [23].…”
Section: Introductionmentioning
confidence: 99%